VREDE TE MIDDE VAN GEWELD:: VERSKEIE PERSPEKTIEWE IN DIE TWAALF KLEIN PROFETE - Scheffler, E (Acta Theologica, 2018)
PEACE AMIDST VIOLENCE: VARIOUS VIEWS IN THE TWELVE MINOR PROPHETS Amidst many perspectives on violence in the Twelve Minor Prophets, there also exist various views on peace. The article focusses on the major peace traditions in the Dodekapropheton and explores the differences in perspectives by the various authors. Of note is the relation between peace and (corroborated) violence, and the context(s) under which conditions for peace are possible. The article also reflects on the psychological issue (referring to Freud’s concepts of eros and thanatos) of how human prophets advocate both peace and violence, involving the concept of God in the process.